Legal and Illegal Immigration in an Efficiency Wage Model - Kenji Kondoh (European Regional Science Association (ERSA), 2001)
In the developed countries like EU and Japan, some young native people dare to enjoy voluntary unemployment. Though they can easily find relatively low-wage job, they prefer to work part-time and look for a chance to to get high-wage job. Moreover the illegal unskilled foreign (legal skilled foreign [or domestic but from different region]) workers are complementary (substitutional) to the natives of that region and their wage is usually low (high). Reflecting this situation, we introduce two types of immigrants in an efficiency wage model (with two different job-sectors) by Shapiro and Stiglitz. The co-existence of these immigrants also permits us to analyze the importance of legality.
Keywords: 330